STUDENTS’ TRANSLATION TECHNIQUES IN TRANSLATING “SLEEPING BEAUTY BY CHARLES PERRAULT” - Neri Herdiawati (Journal of English Education Program (JEEP), 2015)
This is a study about an analysis of translation techniques in short story “Sleeping Beauty” by Charles Perrault. The aims of this study is to investigate the translation techniques used and figure out the most dominant techniques used by the student translators in translating Sleeping Beauty” by Charles Perrault into Bahasa. The method applied in the study is descriptive qualitative, whereas in analyzing the data using translation technique theory from Molina and Albir (2002). The source of the data in this study is short story “Sleeping Beauty” by Charles Perrault. The population were 35 students of 4th Year of English Faculty Galuh University Ciamis. Six students used as the sample to become student translators. The writer used content analysis in finding out the data. From these data the writer found that the result of the study showed that there were five translation techniques used by the translators, they were : literal with 66 use (31,42%), modulation with 62 use (29,52%), reduction with 38 use (18,10%), addition with 35 use (16,66), and transposition with 9 use (4,29%). Literal technique was the most dominant used in translating short story “Sleeping Beauty” by Charles Perrault. There is major implication of this study, this study is improving students’ translation skill. Based on this study results, it is recommended to the lecturers to provide training in text translating into text that easy to understand its content and meaning. Also for further researchers it is recommended to do more researches about techniques in translation.